Algorithm optimization of Er-doped Superfluorescent Fiber Source Feedback Control Module - Zhang, Enkang; Xue, Bing; Yang, Liu; Liu, Yuanheng; Gao, Zhongxing; Zhang, Yonggang (Chinese Control Conference, 2019)
Feedback control module, as an important unit that exists in the Er-doped superfluorescent fiber source's (ED-SFS's) circuit system, shows high significance to the output characteristics of ED-SFS. In this paper, we put forward an optimized feedback control module scheme utilizing the incremental differential-ahead proportion-integral-derivation (IDA-PID) control algorithm. We theoretically analyze this control algorithm and compare it with the other two PID control algorithms. The experimental results show that, with the IDA-PID algorithm, the output power stability of ED-SFS can be reduced from 2.13% to 1.65%, and the mean wavelength thermal stability can be reduced from 261ppm to 148ppm over one hundred degrees Celsius (-40°C~+60°).